The differentially methylated region of MEG8 is hypermethylated in patients with Temple syndrome. (October 2015) - Bens, Susanne; Kolarova, Julia; Gillessen-Kaesbach, Gabriele; Buiting, Karin; Beygo, Jasmin; Caliebe, Almuth; Ammerpohl, Ole; Siebert, Reiner
Aim: To investigate the DNA-methylation levels in the newly described MEG8 differentially methylated region (DMR) in the imprinted cluster in 14q32 in patients with Temple syndrome.Patients & methods: We included three patients with Temple syndrome which were studied by Infinium HumanMethylation450 BeadChips, locus-specific bisulfite-pyrosequencing, methylation-specific-MLPA and microsatellite analyses. The tag-CpG of the MEG8 -DMR was investigated using the Infinium HumanMethylation450 BeadChip.Results: In all three patients, the identical pattern of DNA-hypermethylation of the MEG8 -DMR was observed along with DNA-hypomethylation of the IG-DMR and MEG3 -DMR.Conclusion: Based on the observed MEG8 -DMR DNA-hypermethylation and previously published data, we conclude that DNA-methylation of the MEG3 - and MEG8 -DMR is functionally dependent on the DNA-methylation pattern of the IG-DMR. The observed combination of epimutations is predicted to be associated with bi-allelic MEG3 and MEG8 expression in individuals with Temple syndrome.